2016
DOI: 10.1007/s40620-016-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel score to predict the risk of acute kidney injury in patient with acute myocardial infarction

Abstract: A simple score using clinical and laboratory data available on admission can predict the risk of AKI in patients presenting with acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 19 publications
5
32
1
Order By: Relevance
“…A majority of the published studies showed that basal renal dysfunction was the major risk factor for AKI [11, 22, 23, 32]. Our study confirmed this also.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A majority of the published studies showed that basal renal dysfunction was the major risk factor for AKI [11, 22, 23, 32]. Our study confirmed this also.…”
Section: Discussionsupporting
confidence: 90%
“…In the previous two prediction scores created by Queiroz and Abusaada, tachycardia was an independent risk factor for AKI and was included in the prediction score [22, 23]. The similar conclusion was drawn from our study: we found the risk of AKI increased by 1.75 times when heart rate > 100 bpm at admission.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations